Patient characteristics of deceased organ donors in Switzerland 1998–2008 (Swiss Medical Weekly, 2011)
BACKGROUND: Transplantation today faces two major issues: organ shortage, and the increasing age of deceased donors. The former leads to growing waiting lists and, as a consequence, to a higher mortality of patients in need of an organ. The latter results in an augmentation of the proportion of organs from so called extended criteria donors, which, in the past, have been associated with inferior outcomes. METHODS:Retrospective analysis of the patient characteristics of all deceased organ donors in Switzerland from 1 January 1998 to 31 December 2008. A total of 1004 patient records of brain-dead organ donors (59.4% male, 40.6% female) were analysed for demographic data and causes of death. RESULTS:The average donor age increased from 43.8 ± 16.9 years in 1998 to 51.7 ± 18.0 years in 2008 (+27.6%; p